Bilateral Transmigration of Impacted Mandibular Canines - A Rare Case Report - Suwarna B Dargore; S S Degvekar; R R Bhowate; A D Indurkar (Wolters Kluwer Medknow Publications, 2006)
Pre-eruptive migration of a tooth across the midline is termed "transmigration". This condition occurs with mandibular canines only. In this article, a rare case of bilateral transmigration of mandibular canines along with horizontally impacted maxillary canines is discussed.